Multi-criteria analysis for Life Cycle Assessment and Life Cycle Costing of lightweight artificial aggregates from industrial waste by double-step cold bonding palletization. (1st June 2022) - Petrillo, Antonella; Colangelo, Francesco; Farina, Ilenia; Travaglioni, Marta; Salzano, Cinzia; Cioffi, Raffaele
Abstract: In recent years, the use of recycled materials in the building sector has attracted increasing interest. In this regard, lightweight artificial aggregates are an excellent alternative to natural concretes. This research propose a multicriteria model for the selection of lightweight artificial aggregates through experimental processes. The mechanical, environmental, and economic aspects of the lightweight artificial aggregates were integrated to evaluate the most sustainable, which may be appropriate for applications in the construction sector. Three mixtures were prepared using cement and industrial waste: fly ash from a municipal waste incineration plant, ground granulated blast furnace slag, and marble sludge. The fly ash content is constant (80%). By varying the blast furnace slag (5%, 10%, 15%) and cement content (15%, 10%, 5%), the mechanical, environmental, and economic properties of each lightweight artificial aggregates mix were evaluated. The AHP was implemented to support the identification of preferred scenarios with reference to the three mixtures, on which there may be convergence and compliance in terms of environmental impacts (measured through LCA) and economic (evaluated with the LCC) and technical-functional aspects. The results indicated that lightweight artificial aggregates with fly ash (80%), blast furnace slag (5%) and a higher percentage of cement (15%) represent the optimal solution, which made the sustainable selection of lightweight artificial aggregates possible.